Physicians and nurses experiences of providing care to patients within a mobile care unit - a qualitative interview study - Christofer Teske; Ghassan Mourad; Micha Milovanovic (BMC, 2024)
Abstract Introduction There is a growing need for alternative forms of care to address citizen demands and ensure a competent healthcare workforce across municipalities and regions. One of these forms of care is the use of mobile care units. The aim of the current study was to describe physicians and nurses experiences of providing care to patients within a mobile care unit in Sweden. Method Data were collected between March 2022 and January 2023 through qualitative interviews with 14 physicians and nurses employed in various mobile care units in different regions in Sweden. These interviews were transcribed verbatim and subjected to content analysis, with the study adhering to the Standards for Reporting Qualitative Research (SRQR). Results The analysis resulted in two main categories: "Unlocking the potential of mobile care", and "The challenges of moving hospitals to patients' homes"; and seven subcategories. The respondents viewed mobile care at home as highly advantageous, positively impacting both patients and caregivers. They believed their contributions enhanced patients' well-being, fostering a welcoming atmosphere. They also noted receiving more quality time for each patient, enabling thorough assessments, and promoting a person-centered approach, which resulted in more gratifying mutual relationships. However, they experienced that mobile care also had challenges such as geographical limitations, limited opening hours and logistical complexity, which can lead to less equitable and efficient care. Conclusions Physicians and nurses in mobile care units emphasized positive outcomes, contributing to patient well-being through a person-centered approach. They highlighted increased quality time, comprehensive assessments, and overall satisfaction, praising the mobile care unit's unique continuity for enhancing safety and fostering meaningful relationships in the patient's home environment. In order for mobile care to develop and become a natural part of healthcare, challenges such as geographical limitations and logistics need to be addressed.